Pengaruh Budaya Organisasi Terhadap Kinerja Pegawai Dinas Koperasi Usaha Mikro dan Perindag Kabupaten Gresik - Nira Ayu Monica (Governance, JKMP (Governance, Jurnal Kebijakan & Manajemen Publik), 2020)
Culture is a general description of beliefs, habits, norms, values, behaviors, and ways of doing business that are unique to organizations that regulate patterns of activities and actions of the organization and describe behaviors, implicit patterns and emotions that arise so that it becomes organizational characteristics. Implementation of employee performance can be seen from the implementation of culture in the organization. The more culture is built well, the results obtained are also getting better. The problem raised by the author is whether Organizational Culture influences the Performance of Employees of the Cooperative Office of Micro Enterprises and Industry and Trade Gresik Regency. all employees of the Gresik Regency Cooperative Office of Micro Enterprises and Industry and Trade have used total sampling techniques. Data collection using a questionnaire, which was given directly to respondents as many as 26 employees. The results of the study showed that organizational culture had a positive and significant effect on the performance of employees of the Cooperative Office of micro-businesses and district gresik industries, so that the First Hypothesis (H1) was accepted in this study.